Design and manufacturing of a patient-specific nasal implant for congenital arhinia: Case report. (September 2019) - Borghi, Alessandro; Ruggiero, Federica; Tenhagen, Maik; Schievano, Silvia; Ponniah, Allan; Dunaway, David; O'Hara, Justine; Ong, Juling; Britto, Jonathan A.
Abstract: Arhinia (congenital absence of the nose) is a congenital rare disease, which has been reported in less than 60 cases in the literature. It consists of the absence of external nose, nasal cavities and olfactory apparatus and is generally associated with midline defects, microphthalmia, blepharophimosis and hypotelorism. Aesthetic problems as well as associated functional anomalies can potentially impact on the development and interpersonal relationships of the child at a later stage in life. Arhinia requires extensive management in early life in order to ensure airway patency and protection by means of tracheostomy, and to allow adequate pharyngeal and feeding function to the child. Aesthetic issues are managed with reconstructive surgery or an external prosthesis. There is no previous description in Literature of internal prosthetic devices used to sequentially shape soft tissues in complex reconstruction. We present an example of design and manufacturing of a bespoke nose implant produced by means of 3D printing and directly assessed on-table by means of 3D surface scanning.